Triggering of NF-κB in cytokine-matured human DCs generates superior DCs for T-cell priming in cancer immunotherapy. - Pfeiffer, Isabell; Hoyer, Stefanie; Gerer, Kerstin; Voll, Reinhard E.; Knippertz, Ilka; Gueckel, Eva; Schuler, Gerold; Schaft, Niels; Dörrie, Jan (European Journal of Immunology, 2014)
Understanding the signaling that governs the immunogenicity of human dendritic cells (DCs) is a prerequisite for improving DC-based therapeutic vaccination strategies, in which the ability of DCs to induce robust and lasting Ag-specific CTL responses is of critical importance. Cytokine-matured DCs are regularly used, but to induce memory-type CTLs, they require additional activation stimuli, such as CD4+ T-cell help or TLR activation. One common denominator of these stimuli is the activation of NF-?B. Here, we show that human monocyte-derived, cytokine cocktail-matured DCs transfected with constitutively active mutants of I?B kinases (caIKKs) by mRNA electroporation, further upregulated maturation markers, and secreted enhanced amounts of cytokines, including IL-12p70, which was produced for more than 48 h after transfection. Most importantly, cytotoxic T cells induced by caIKK-transfected DCs combined high CD27 expression, indicating a more memory-like phenotype, and a markedly enhanced secondary expandability with a high lytic capacity. In contrast, CTLs primed and expanded with unmodified cytokine cocktail-matured DCs did not maintain their proliferative capacity upon repetitive stimulations. We hypothesize that "designer" DCs expressing constitutively active I?B kinases will prove highly immunogenic also in vivo and possibly emerge as a new strategy to improve the clinical efficacy of therapeutic vaccinations against cancer and other chronic diseases.
EVALuna2:19501